(untitled) (Eurasian Research Bulletin, 2023)
Fluoride (F) is an element that occurs naturally on earth. Exposure to fluoride has negative effects on the human body and the intake mainly depends on what the person is consuming i.e. food, water, and air. Accumulation of fluoride occurs after continuous exposure to it as it can take 20 years or more to become evident and studies have shown that it affects various body parts including the renal, liver, and central nervous system.